Advanced Encryption Standard (AES) Cryptography Application Design - Allwine, Allwine; Atim, Sandi Badiwibowo; Afdhaluddin, Muhammad (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2025)
As technology advances, the need for secure data transmission and storage increases. Encryption and decryption are essential processes to ensure data confidentiality and integrity. Encryption transforms original data into unreadable form during transmission, while decryption restores it to its original state for the recipient. This guarantees that unauthorized parties cannot access the data. Cryptosystems have evolved over time, and with the rapid growth of communication technologies, stronger standards are needed. AES (Advanced Encryption Standard), based on the Rijndael algorithm, has become the current standard for encryption. AES can encrypt and decrypt 128-bit data blocks with key lengths of 128, 192, or 256 bits, addressing the limitations of older algorithms and providing enhanced data security to protect confidentiality in modern cryptosystems.